The Asymmetric Effects of Oil Price Changes on the Economic Activities in Indonesia - Rina Juliet Artami; Yonosuke Hara (Signifikan: Jurnal Ilmu Ekonomi, 2018)
This paper analyzes the asymmetric impact of oil price changes on the economic growth of and inflation in Indonesia by using the vector autoregression (VAR) model for the period from 1990Q1 to 2016Q4. The results show that the impact of oil price changes on the gross domestic product (GDP) is asymmetric, as a drop in oil prices decreases the GDP, whereas an increase in oil prices does not significantly affect GDP. It is crucial for Indonesia to reduce its dependency on oil, mainly as its primary source of revenue, and also consider utilizing more sources of renewable energy. At the same time, the effects of both the positive and negative changes in oil prices are found to be not statistically significant to inflation. The lack of impact of oil price changes on inflation can explain by the implementation of the fuel price subsidy in Indonesia.DOI: 10.15408/sjie.v7i1.6052